The Girls from Brazil - Tal, Nili (YES Docu, 2007)
Verzio FF Submission About 3000 children were adopted in Brazil in the 80s by Israeli families. These children are now grown-up and some of them are traveling to their land of origin to look for the women who gave birth to them. This is the story of four of them.